(3MOjK YbHI Hf YGeQ HYddg ddbGVi CHj HcQ Hf GdYQHis - (3eMeO Hf YHO Gddg Hf eMeO GdeYGaQj GdETHjdj GdeGdcj, GdbGVj CHh HcQ GHf GdYQHqj , J (B543 (3g` s ((3eOjfI ZQfGWI s)
(3ChdgG (B:s
(3CNHQfG GdTjN Gdabjg GdEeGe CHh YHO Gddg eMeO Hf EHQGgje Hf Nda Hf CMeO GdCfUGQi aCOQcJ QShd Gddg Udi Gddg Ydjg hSde hgh bGFe jMOK GdfGS s
(3BNQgG (B:s
(3Cf GdMOjK Med Ydi ZjQg hQcH Ydi ShGg bUOkG Ch ZdWkG ced MOjK YbHI Hf YGeQ HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3eUOQ GbJfGA GdCUd (B:s
(3eOQjO (B(5349) s
Keywords: (3GdMOjK h GdeUWdMs